Réponses

2014-10-15T20:37:10+02:00
a=(7x+3)²-(x+2)(2x-9)
  =(7x)²+2*7x+3+3²-(x*2x+x*(-9)+2*2x+2*(-9))
  =49x²+42x+9-(2x²-9x+4x-18)
  =49x²+42x+9-2x²+9x-4x+18
  =47x²+47x+27

b=(2x-3)(5-x)-(2x-3)²
  =2x*5+2x*(-x)-3*5-3*(-x)-((2x)²-2*2x*3+3²)
  =10x-2x²-15+3x-(4x²-12x+9)
  =10x-2x²-15+3x-4x²+12x-9
  =-6x²+25x-24

voilà ;)
2014-10-15T20:38:13+02:00


A = (7x + 3)² - (x + 2) (2x - 9)

A = 7x² + 42x + 9 - (2x² - 9x + 4x - 18)

A = 7x² + 42x + 9 - 2x² + 9x - 4x + 18

A = 5x² + 47x + 27


B = (2x - 3) (5 - x) - (2x - 3)²

B = (10x - 2x² - 15 - 3x) - (2x² - 12x + 9)

B = 10x - 2x² - 15 - 3x - 2x² + 12x - 9

B = - 4x² + 19x - 24